Women business leaders - Jamjoom, Liela A. ([S.l.])
1 online resource
Keywords: Published works on Saudi women in organizational contexts are overwhelmingly reductionist, producing a singular story and a monolithic "Saudi woman." This book aims to counter the master narrative on Saudi women in leadership by offering an intimate reading of the women's stories and experiences. The author interviews14 Saudi women leaders focusing on the women's stories of leadership identity, workplace "resistance," and alternative forms of knowledge. From a methodological standpoint, the reader is given the opportunity to encounter the women at three different levels of analysis: Master narrative, counter narratives, and my narrative. There is also a theoretical discussion surrounding a variety of feminisms: Postcolonial feminism, Islamic feminism, and Decolonial Feminism. This theoretical engagement will enable readers to understand the difficulty of the theoretical terrain, while also acknowledging the possibility for future theory development. Expanding on previous studies on Saudi women in leadership by taking the discussion away from challenges to the ways in which the women navigate those challenges, this book serves as an emancipatory and inclusive tool in research with practical implications in business. This book will be of value to researchers, academics, and professionals in the fields of leadership, management, gender, and diversity.